Mass Distribution of Particulate Matter Produced During Abrasion af Asphalt Mixtures in Laboratory - Fullova, Dasa; Durcanska, Daniela; Jandacka, Dusan; Estokova, Adriana (Communications - Scientific letters of the University of Zilina, 2016)
Non-exhaust emissions of particulate matter from road traffic can come from abrasion of vehicle parts (tyres, brake linings, clutch and bodywork) or from pavement surface abrasion and also from resuspension of dust. A differentiation between PM emissions from road pavement abrasion and resuspension is very difficult due to their similar elemental composition. The research is focused on abrasion of pavement surface from asphalt mixtures. Experimental tests are conducted for measuring of particulate matter production in the atmosphere during the rutting of various asphalt mixtures used for wearing courses. The tests are performed in wheel tracking machine in the laboratory. Particle sampling in the laboratory makes it possible to sample PM with very low contamination from surrounding sources and no influence from exhaust emissions. The paper presents an example of the results of measurements on six trial samples of asphalt mixtures with different composition.